2021
DOI: 10.3389/fpsyt.2021.537383
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences Related to Spirituality, Coping Skills and Risk Factors of Suicide Attempt: A Cross-Sectional Study of French Adolescent Inpatients

Abstract: Background: Suicide attempts in adolescence represent a major public health concern, since these behaviors are associated with psychosocial burden and an increased risk of suicide. This cross-sectional study aimed to explore possible gender differences related to protective and risk factors in adolescents who have attempted suicide.Methods: Participants were French adolescents hospitalized for attempt suicide in five French pediatric departments. The participants were evaluated on 12 instruments measuring indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…Finally, in the SI literature, gender disparities in suicide susceptibility have not been well addressed [ 50 ]. Emerging research aims to highlight possible gender variations in suicide risk vulnerability (i.e., behavior and ideation).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in the SI literature, gender disparities in suicide susceptibility have not been well addressed [ 50 ]. Emerging research aims to highlight possible gender variations in suicide risk vulnerability (i.e., behavior and ideation).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, however, reported that women use spirituality differently than adolescent men. For example, girls had a significantly higher overall spirituality score than boys and were more self-aware and collectively conscious (Mirkovic et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This study did not refine the selection of the study population to refer to the public group in general, and future research needs to focus on specific occupational field groups and integrate the characteristics of their work to research coping capacity. In addition, a number of studies have concluded that there are gender differences in stress and coping with stress [ 29 , 30 ], so future studies will be supplemented with corresponding studies that take into account the impact of gender differences on the ability to cope with public health emergencies.…”
Section: Discussionmentioning
confidence: 99%